A Saudi National population based study Awareness and Practice of Periodic Medical check-up (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: The periodic medical examination is important in preventing some diseases and reducing their majorcomplications; thus, it’s beneficial to provide a better healthy community and reducing financial loss. Studyingbeliefs, awareness, practice, and influence factors in the community will be a useful method to promote healthamong the population. Materials and Methods: Cross-sectional study survey in different areas in Makkah regionusing a sampling technique the sample size was 2061 participants of both gender. Data were collected through aself-administered structured survey. Results and Discussion: Adults 20–39 years (899) (56.9%) were the mostgroup which have adequate knowledge. The most aware participants were females (928) (58.7%). 1021 (66.4%)of the aware participants have academic educational level. Most participants did not recall performing any medicalcheckup (1607) (78.0%). Conclusion: We noticed in this study that the rate of awareness of the participantswas high but unfortunately it did not show reflection on their behavior toward medical checkups. This poorimplementation despite their awareness was justified mostly by two major factors which were negligence andabsence of motivation.